Development and characterization of electrical heating garment based on the weft knitted jacquard pattern for back pain disease. Issue 11 (26th October 2022) - Liu, Su; Fu, Shaoju; Wu, Jun; Li, Shi
Abstract: Applying knitted technologies on electrical heating garment on curing back pain with infrared physiotherapy method has been more and more popular recently. However, the relationship between the knitting technics and their electrothermal properties of fabric and garments were still unclear. Hence, different types of fabrics with varied configuration of conductive path based on weft knitted jacquard pattern (WKJP) and their garments were fabricated in this work, and the temperature variation of them were adopted to verify the feasibility of this method. The results showed that the temperatures were belonged to 30-35 °C, which satisfied the needs of heating for human body. Fabrics with a concentration of 60% sliver yarns showed the most suitable heating behavior, and the fabricated garments provided the most stable heating area, which was suitable for the human body. In sum, the paper gives out an orientation and guidance for the development and characterization of electrical heating garment and related products.